Treatment of Acute Schistosomiasis mansoni with Praziquantel and an Antifibrotic Agent in Mice - Hassan, Soad Ismail; Ali, Iman; Nessim, Nevine Guirguis; Amer, Neemat Moussa; Khafif, Mohamed Abd El Kader El; Ashour, Amin; Mohandes, Mohamed El (Arzneimittelforschung, 2003)
This work is a trial to evaluate the effect of the combination of the anthelmintic drug praziquantel (CAS 55268-74-1, PZQ, EMBAY 8440, Biltricide®) with the antifibrotic agent β-aminopropionitrile-monofumarate salt (BAPN, CAS 2079-89-2). It is also a trial to elucidate the repercussions of this drug combination upon worm and tissue egg loads and oogram pattern. Moreover, it aims to study their effects on the hepatic granuloma size and the resistance to reinfection in experimental murine schistosomiasis mansoni.A group of 120 Swiss albino mice was used. This group was further subdivided into six small subgroups. Subgroup I comprised infected untreated control mice. Subgroup II comprised infected untreated challenged contol mice. Subgroup III comprised challenged control mice. Subgroup IV comprised infected mice treated with PZQ 500 mg/kg b. w. orally for two successive days. Subgroup V comprised infected mice given BAPN daily as 5 mg powder in 0.5 ml saline for 14 successive days. Subgroup VI comprised mice given both PZQ + BAPN. Animals were sacrificed 12 weeks post primary infection.Mice given the combination regimen PZQ + BAPN, compared to those given each drug solely, revealed absence of worm recovery at perfusion and only dead ova in the oogram (99.2 + 0.6). Inspite of the marked reduction in the hepatic and intestinal tissue egg loads recorded, this drug combination revealed the highest score of percent resistance to reinfection (91.2 + 0.5 %). The data were less salient in mice given PZQ or BAPN alone.
Keywords: β-Aminopropionitrile monofumarate, combination with praziquantel; CAS 2079-89-2; CAS 55268-74-1; Biltricide®; EMBAY 8440; Praziquantel, combination with β-aminopropionitrile monofumarate; Schistosomiasis mansoni, primary and secondary infection